Classification Of Spare Parts For CO2 Compressor At PIM-1 Plant Using Integration Of Multi-Criteria Analysis And Forecasting Model Determination With Single Exponential Smoothing Method (Case Study: PT Pupuk Iskandar Muda) - Faryani, Lena; Irwanysah, Irwanysah; Fradinata, Edy (International Journal Labs, 2025)
PT Pupuk Iskandar Muda (PIM), a subsidiary of PT Pupuk Indonesia (Persero), plays a pivotal role in supporting national food security through the reliable operation of its fertilizer plants. Effective spare parts inventory management is crucial to ensure uninterrupted plant operations. However, challenges arise due to the high volume of spare parts managed and the intermittent or lumpy nature of demand. Inefficient inventory management has led to stockpiling of certain items and shortages of frequently used materials. This study aims to classify spare parts used in the CO? Compressor of PIM-1 Plant using a multi-criteria analysis method, considering critical factors related to maintenance and logistics. The classification categorizes spare parts into three groups: high, medium, and low. Out of 20 spare parts analyzed, 18 items were classified as high priority (requiring stock), while 2 items were classified as low priority (non-stock). Forecasting for the 18 high-priority items was conducted using three methods: Single Exponential Smoothing (SES), Syntetos-Boylan Approximation (SBA), and Croston. The forecasting errors were evaluated using the Mean Absolute Deviation (MAD). The results indicated that SES yielded the smallest error with an average MAD of 2.15, compared to SBA (2.24) and Croston (2.37). Implementing this approach resulted in a 22% reduction in inventory costs, decreasing the estimated inventory cost for 2023 from IDR 3.428 billion to IDR 2.681 billion. This demonstrates the importance of applying appropriate methods in spare parts management to enhance operational efficiency and support the company's objectives.